Association of pre-ESKD hyponatremia with post-ESKD outcomes among incident ESKD patients. Issue 2 (13th August 2021) - Marroquin, Maria V; Sy, John; Kleine, Carola-Ellen; Oveyssi, Justin; Hsiung, Jui-Ting; Park, Christina; Soohoo, Melissa; Kovesdy, Csaba P; Rhee, Connie M; Streja, Elani; Kalantar-Zadeh, Kamyar; Tantisattamo, Ekamol
Abstract: Background: Hyponatremia is one of the most common electrolyte disturbances in advanced chronic kidney disease (CKD) and end-stage kidney disease (ESKD) patients, and has been shown to be associated with higher mortality risk. However, the relationship between hyponatremia during late-stage CKD and the risk of poor outcomes after ESKD transition is unknown. Methods: We conducted a retrospective cohort study including 32 257 US veterans transitioning to ESKD from 1 October 2007 to 30 March 2015. We evaluated adjusted associations between the 3-month averaged pre-transition to ESKD serum sodium and all-cause mortality. Secondary outcomes included cardiovascular (CV) mortality, infection-related mortalities and hospitalization rate. Results: Cohort mean ± standard deviation serum sodium was 139 ± 3 mEq/L, mean age was 67 ± 11 years, 98% were male and 28% were African American. Over a median (interquartile range) follow-up of 702 days (296, 1301) there were 17 162 deaths. Compared with the reference of 135 to <144 mEq/L, the lowest serum sodium group (<130 mEq/L) had a 54% higher all-cause mortality risk [hazard ratio 1.54 (95% confidence interval 1.34–1.76)] in the fully adjusted model. Associations were similar for CV and infection-related mortality, and hospitalization outcomes. Conclusions: Hyponatremia prior to ESKD transition is associated with higher risk of all-cause, CV and infection-related mortalities, and hospitalization rates after ESKD transition. Future studies evaluating management of pre-ESKD hyponatremia may be indicated to improve patient outcomes for those transitioning to ESKD.